Impact on Educational Effectiveness Using Digital Gamification - Alyusha Asmolov; Avraam Ledentsov (Pandawan Sejahtera Indonesia, 2023)
This study's objective was to evaluate the educational value and motivational pull of computer games created with Greek secondary school curricula in mind for the study of computer memory principles. Comparing it to related applications, computer science (CS) encompasses goals and substance. similar learning, but without the gaming element. This study also looks into possible gender differences in learning efficiency and the appeal of play as a motivator. The sample consisted of 88 students who were separated into two groups at random: one group that used game applications (Group A, N = 47) and one group that did not use game applications (Group B, N = 41). Both the pretest and the posttest employed the Computer Memory Knowledge Test (CMKT). The intervention was also seen by students. Additionally, following the intervention, students' opinions of the applications they had used were solicited via a feedback form. Data analysis revealed that compared to the non-game approach, the game approach was more effective in improving students' understanding of computer memory concepts and more motivating. The learning outcomes that boys and girls achieve through game use are not significantly different, and games were found to be the same. This is true even though boys have more involvement with, a greater preference for, and experience with computer games. They also have a greater prior knowledge of computers. girls' and boys' inspiration The findings demonstrate that, regardless of the gender of the students, educational computer games may be used as an effective and inspiring learning environment in secondary school CS.